PENGARUH KONDISI EKOSISTEM DARAT KORIDOR SUNGAI TERHADAP DANAU RAWA PENING - Sittadewi, E. Hanggari (BPPT)
Environment degradation in Rawa Pening?s lake is caused of descend lake?s functions for some potentions and activities around the lake. Some problems in the Rawa Pening?s lake has emerged i.e : decrease water quality of lake, abundance of water hyacinth growth and increase sediment in the bottom lake. A research about infl uences of land ecosystem on Panjang and Galeh river corridors for Rawa Pening?s lake has been done. Two rivers named Galeh and Panjang are the largest water contribution in Rawa Pening?s lake. That caused the land characteristic ecosystem of that river corridors gives infl uences in the Rawa Pening?s lake.Key words: land ecosystem, river corridor, water contribution, Rawa Pening Lake.